Persistent Intrinsic Functional Network Connectivity Alterations in Middle-Aged and Older Women With Remitted Depression - Vega, Jennifer N.; Taylor, Warren D.; Gandelman, Jason A.; Boyd, Brian D.; Newhouse, Paul A.; Shokouhi, Sepideh; Albert, Kimberly M. (Frontiers in Psychiatry, 2020)
Background: In younger adults, residual alterations in functional neural networks persist during remitted depression. However, there are less data for midlife and older adults at risk of recurrence. Such residual network alterations may contribute to vulnerability to recurrence. This study examined intrinsic network functional connectivity in midlife and older women with remitted depression. Methods: 69 women (24 with a depression history, 45 with no psychiatric history) over 50 years completed 3T fMRI with a resting state acquisition. Participants with remitted depression met DSM-IV-TR criteria for an episode in the last 10 years, but not the prior year. Whole-brain seed-to-voxel resting-state functional connectivity analyses examined the default mode network (DMN), executive control network (ECN), and salience network (SN), plus bilateral hippocampal seeds. All analyses were adjusted for age and used cluster-level correction for multiple comparisons with FDR < 0.05 and a height threshold of p < 0.001 uncorrected. Results: Women with a history of depression exhibited decreased functional connectivity between the SN (right insula seed) and ECN regions, specifically the left superior frontal gyrus. They also exhibited increased functional connectivity between the left hippocampus and the left postcentral gyrus. We did not observe any group differences in functional connectivity for DMN or ECN seeds. Conclusions: Remitted depression in women is associated with connectivity differences between the SN and ECN, and between the hippocampus and the postcentral gyrus, a region involved in interoception. Further work is needed to determine whether these findings are related to functional alterations or are predictive of recurrence.